Ta’tsir Kafaah Mu’allimiy Al Lughah Al ‘Arabiyyah fi Natiijah Maharah Al Kitabah Ladaa Thalabah Al Madaaris Al Tsanawiyyah Al Islamiyyah Al Hukumiyyah bi Mujukirtu - Noviya Ekasanti; Wildana Wargadinata; Nur Ila Ifawati (Rumah Jurnal IAIN Bukittinggi, 2021)
Teachers are the heart of an education, which through their abilities will be born a young generation who is ready to become a reliable national cadre in all fields. Every teacher is required to have competence in accordance with National Education Standards because teacher competence is considered to have an effect on student learning outcomes. The purpose of this study is to determine the magnitude of: 1.The influence of pedagogical competence 2.The Influence of the Personality Competence. 3.The influence of Social Competence. 4.The influence of Professional Competence of Arabic Language Teachers on the learning outcomes of students' writing skills at MAN Mojokerto. This study uses a quantitative research design. The data analysis model used is Simple Linear Regression with the help of the IBM SPSS 22 application. The results of this study indicate that: 1.The pedagogic competence is in the good category with a significance = 0.001. The magnitude of the influence of teacher pedagogic competence is 65.4% affecting the learning outcomes of writing skills, while the rest is influenced by other factors. 2. Personality competence is good with a significance = 0.021. The magnitude of the teacher's personality competence 43% affects the learning outcomes of writing skills, while the rest is influenced by other factors. 3. Social competence is good with a significance = 0.004. The magnitude of the teacher's personality competence 57.9% affects the learning outcomes of writing skills, while the rest is influenced by other factors. 4. The professional competence is good with a significance = 0.003. The ratio of teachers' professional skills is 60.1% which affects the learning outcomes of writing skills, while the rest is influenced by other factors.The formal findings of this study are: Teacher competence has an effect on student learning outcomes. Simultaneously, the influence of pedagogic, personality, social, and professional competence is significant on student learning outcomes in writing skills. This means that if teacher competence increases, it will be followed by increased student learning outcomes. Or vice versa if teacher competence decreases, student learning outcomes will also decrease.إن المعلمين قلب التعليم، وبقدراتهم يمكن أن يطبع جيل الشباب كادر الأمة الموثوقة في جميع المجالات. فيجب أن يكون كل معلم مؤهلًا بالكفاءة وفقًا لمعايير التعليم الوطنية ، لأن كفاءة المعلم تعتبر ذات تأثير على نتيجة تعلم الطلبة. والغرض من هذا البحث هو لقياس: 1. تأثير الكفاءة التعليمية 2. تأثير الكفاءة الشخصية 3. تأثير الكفاءة الاجتماعية 4. تأثير الكفاءة المهنية لمعلمي اللغة العربية في نتيجة تعلم مهارة الكتابة لدى الطلبة في المدارس الثانوية الإسلامية بموجوكرتو. تستخدم هذه الدراسة تصميم بحث كمي. وأسلوب تحليل البيانات المستخدم هو الانحدار الخطي البسيط بمساعدة تطبيق IBM SPSS 22. ونتائج هذه الدراسة إلى ما يلي: 1. الكفاءة التعليمية في فئة جيدة مع أهمية = 0.001 وحجم تأثير الكفاءة التعليمية للمعلمين 65.4٪ تؤثر على نتيجة تعلم مهارة الكتابة بينما تتأثر الباقية بعوامل أخرى 2. الكفاءة الشخصية جيدة مع دلالة = 0.021. يؤثر حجم كفاءة شخصية المعلمين 43٪ على نتيجة تعلم مهارة الكتابة، بينما يتأثر الباقي بعوامل أخرى.3 . الكفاءة الاجتماعية جيدة مع دلالة = 0.004 حجم كفاءة شخصية المعلمين 57.9٪ تؤثر على نتيجة تعلم مهارة الكتابة ، بينما يتأثر الباقي بعوامل أخرى 4. الكفاءة المهنية جيد مع دلالة = 0.003. نسبة المهارة المهنية للمعلمين 60.1٪ مما يؤثر على نتائج تعلم مهارة الكتابة، بينما يتأثر الباقي بعوامل أخرى. والنتائج الرسمية لهذه الدراسة هي كفاءة المعلمين لها تأثير على نتائج تعلم الطلبة. وهناك تأثير كبير على الكفاءة التعليمية والشخصية والاجتماعية والمهنية لمعلمي اللغة العربية على نتائج تعلم مهارة الكتابة لدی الطلبة. وهذا يعني أنه في حالة زيادة كفاءة المعلمين، فسوف يتبع ذلك زيادة في نتائج تعلم الطلبة، أو العكس إذا انخفضت كفاءة المعلمين، فسوف تنخفض أيضًا نتائج تعلم الطلبة.